Media consumption and youth work competencies: Evidence from the Hong Kong youth survey - Boris Lok-Fai Pun; Jeremy Ko; Anthony Ying-Him Fung; Janice Ka-Yee Wong (PLoS ONE, 2026)
This study examines how the number of hours spent on different types of media consumption is associated with youth work‑readiness competencies in Hong Kong. Using survey data from 363 tertiary students across six institutions (October to December 2024), the analysis investigates relationships between weekly hours of exposure to six media forms—newspapers, online media, television, social media, content‑creator channels, and online forums—and three dimensions of work readiness: workplace soft skills, reflection and learning, and career aspiration/planning. Results show that structured and feedback‑rich media, such as newspapers and purposeful social media use, are positively associated with work‑readiness competencies, while unstructured or entertainment‑driven media, including online forums and content‑creator channels, are negatively associated. These findings suggest that not only the quantity but also the quality and structure of media engagement influence the development of key competencies. The study highlights that structured media environments serve as important contexts for learning and skill formation among Hong Kong youth.